Positive allosteric modulation of alpha‐7 nicotinic receptors promotes cell death by inducing Ca2+ release from the endoplasmic reticulum. (6th March 2015) - Guerra‐Álvarez, María; Moreno‐Ortega, Ana J.; Navarro, Elisa; Fernández‐Morales, José Carlos; Egea, Javier; López, Manuela G.; Cano‐Abad, María F.
Abstract Positive allosteric modulation of α7 isoform of nicotinic acetylcholine receptors (α7‐nAChRs) is emerging as a promising therapeutic approach for central nervous system disorders such as schizophrenia or Alzheimer's disease. However, its effect on Ca2+ signaling and cell viability remains controversial. This study focuses on how the type II positive allosteric modulator (PAM II) PNU120596 affects intracellular Ca2+ signaling and cell viability. We used human SH‐SY5Y neuroblastoma cells overexpressing α7‐nAChRs (α7‐SH) and their control (C‐SH). We monitored cytoplasmic and endoplasmic reticulum (ER) Ca2+ with Fura‐2 and the genetically encoded cameleon targeting the ER, respectively. Nicotinic inward currents were measured using patch‐clamp techniques. Viability was assessed using methylthiazolyl blue tetrazolium bromide or propidium iodide staining. We observed that in the presence of a nicotinic agonist, PNU120596 (i) reduced viability of α7‐SH but not of C‐SH cells; (ii) significantly increased inward nicotinic currents and cytosolic Ca2+ concentration; (iii) released Ca2+ from the ER by a Ca2+‐induced Ca2+ release mechanism only in α7‐SH cells; (iv) was cytotoxic in rat organotypic hippocampal slice cultures; and, lastly, all these effects were prevented by selective blockade of α7‐nAChRs, ryanodine receptors, or IP3 receptors. In conclusion, positive allosteric modulation of α7‐nAChRs with the PAM II PNU120596 can lead to dysregulation of ER Ca2+, overloading of intracellular Ca2+, and neuronal cell death. <boxed-text content-type="graphic" id="jnc13049-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> This study focuses on how the type II positive allosteric modulator PNU120596 (PAM II PNU12) affects intracellular Ca2+ signaling and cell viability. Using SH‐SY5Y neuroblastoma cells overexpressing α7‐nAChRs (α7‐SH) and their control (C‐SH), we find that PAM of α7‐nAChRs with PNU120596: (i) increases inward calcium current (ICa) and cytosolic Ca2+ concentration ([Ca2+]cyt); (ii) releases Ca2+ from the ER ([Ca2+]ER) by a Ca2+‐induced Ca2+ release mechanism; and (iv) reduces cell viability. These findings were corroborated in rat hippocampal organotypic cultures. [Ca2+]cyt, cytosolic Ca2+ concentration; [Ca2+]ER, endoplasmic reticulum Ca2+ concentration; α7 nAChR, α7 isoform of nicotinic acetylcholine receptors; α7‐SH, SH‐SY5Y stably overexpressing α7 nAChRs cells; C‐SH, control SH‐SY5Y cells; Nic, nicotine; PNU12, PNU120596.